EFFICIENCY ESTIMATION OF SUPRESSIVE THERAPY OF SEVERE PSORIASIS IN CHILDREN - N.N. Murashkin (Педиатрическая фармакология)
The article gives an analysis of a 5 year observation of psoriatic process among 38 children aged 7 to 17, suffering from severe psoriasis under suppressant therapy. The author concludes that the tactics of active influence on the psoriatic process for children in most cases results in an aggressive form of the disease, resistent to the applied therapy.Key words: psoriasis, children, suppressant therapy.